Public Sector Records Systems in Ghana: Some Lessons in Development Management - Akotia, P. (African Journal of Library, 2003)
The origins of the decline and the revitalisation of the National Archives of Ghana go a long way back. Its near collapse to a large extent was self- inflicted. The result was a progressive deterioration in the management of recorded information, key to the efficiency and effectiveness of government. This article argues that the Ghana Records Management Improvement Programme subsequently introduced as part of the initiative to strengthen the civil service marked a paradigm shift in the development management strategies of Ghana. Restructuring the records management systems of government was crucial for improving the efficiency of development management interventions. The strengthened National Archives has been transformed into a department exercising a wider remit. New systems and procedures have been put in place to provide a sound records management programme. Unable, however, to address the management of financial records alongside records of other sectors, public financial management has remained weak due to the unstructured and poor state of the existing financial records systems. This remains so despite the several policy measures introduced to strengthen financial management
Research Article
Keywords: information management; information; national archives; Ghana